Analysis of the Financial Performance of BPR National Sharia Before and During the Covid-19 Pandemic - Edison Siregar; Riwandari Juniasti; Fery Tobing (Eduvest - Journal of Universal Studies, 2022)
The COVID-19 pandemic and the implementation of Large-Scale Social Restrictions that occurred in Indonesia resulted in an economic slowdown. Then the problem that is present in the banking sector is the difficulty of debtors in fulfilling their credit obligations. The purpose of this study is to analyze the differences in the performance of the National Sharia BPR before the covid 19 pandemic and during the covid 19 pandemic for the period June 2018 - September 2021. In this study, performance was measured by the asset return ratio (ROA), capital adequacy ratio (CAR), ratio of non-performing loans (NPF), operating expenses to operating income (BOPO), and the ratio of loans to deposits (FDR). The research is included in quantitative research with a comparative type. The data used is secondary data in the form of the financial statements of the National Sharia BPR obtained from www.ojk.co.id. Data analysis in this study used paired sample t-test analysis with the help of the SPSS version 25 program. The results showed that only CAR and NPF had significant differences before and during the COVID-19 pandemic. While ROA, BOPO, and FDR had no significant differences. before and during the covid 19 pandemic.